2021
DOI: 10.1039/d0fo02185g
|View full text |Cite
|
Sign up to set email alerts
|

Standardized hot water extract from the leaves of Hydrangea serrata (Thunb.) Ser. alleviates obesity via the AMPK pathway and modulation of the gut microbiota composition in high fat diet-induced obese mice

Abstract: WHS prevented the HFD-induced obesity via regulating AMPK and AKT/mTOR signaling pathway. WHS might be a potential dietary supplement for alleviating obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Ser. (WHS) using high-fat diet (HFD)induced obese mice and found that WHS may exert anti-obesity effects [23]. In addition to poor diet, genetic factors can contribute to the development of obesity [24]; thus, we further expanded our investigation on the weight loss effect of daily intake of WHS and the underlying molecular mechanisms in genetically obese db/db mice in this study.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Ser. (WHS) using high-fat diet (HFD)induced obese mice and found that WHS may exert anti-obesity effects [23]. In addition to poor diet, genetic factors can contribute to the development of obesity [24]; thus, we further expanded our investigation on the weight loss effect of daily intake of WHS and the underlying molecular mechanisms in genetically obese db/db mice in this study.…”
Section: Introductionmentioning
confidence: 95%
“…Total cellular and tissue protein were extracted as previously described [23]. The protein concentration was quantified by Bradford assay (Bio-Rad Laboratories, Inc., Hercules, CA, USA) according to the manufacturer's instructions.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 99%
See 3 more Smart Citations